Developmental stages: an Islamic psychology perspective - Hashim, Mohammad (Journal of spirituality in mental health, 2025)
This study aims to integrate primary sources of Islamic Psychology, Quran and Hadith with psychological models to explore how various stages of life are characterized and developed according to these perspectives. Drawing on sources such as Quranic verses, Hadiths, and psychological theories, the research examines the stages of childhood, puberty, adulthood, maximum maturity, and old age. Findings indicate that Islamic teachings emphasize moral and spiritual growth, while psychological theories focus on cognitive and emotional development. It highlights the alignment and divergence between these approaches, demonstrating that Islamic perspectives on development often intersect with psychological theories but also present unique insights.